Slang and gastronomy - Szabó, Dávid (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
Speakers of non-standard varieties of French also like to eat and have their own words for food. But can gastronomy be considered as a major theme in slang? This paper tries to answer this question by analysing argot and unconventional French dictionaries (Colin et al. 2006, Goudaillier 2001, Tengour 2013, Perret 2002) and works by specialists such as Calvet and Robert L’Argenton. Slang varieties dealt with range from traditional French slang to contemporary suburban slang (français contemporain des cités) and include butchers’ slang (louchébem) and bakers’ jargon. The conclusion also suggests some ideas on teaching French as a foreign language.